Dissociating variations in attention with schizotypy and anxiety - Granger, Kiri Tegan (2017)
Establishing how cognitive abnormalities result in the signs and symptoms that define schizophrenia and anxiety disorders (and their co-morbidity) has become a prominent question in clinically, and sub-clinically, applied research. Abnormal performance in schizophrenia, schizotypy and anxiety has been observed in comparison to healthy individuals on a range of cognitive and behavioural tasks. For example, abnormal attention to irrelevant information has long been recognised by clinicians, which has since encouraged researchers to elucidate the nature of the relationship between schizophrenia, and anxiety more recently, with allocation of attention to stimuli in laboratory studies providing empirical evidence for an attentional view of these disorders.